MicroRNAs are transported in plasma and delivered to recipient cells by high-density lipoproteins - Vickers, Kasey C.; Palmisano, Brian T.; Shoucri, Bassem M.; Shamburek, Robert D.; Remaley, Alan T. (Nature cell biology, 2011)
Circulating microRNAs (miRNA) are relatively stable in plasma and are a new class of disease biomarkers. Here we present evidence that high-density lipoprotein (HDL) transports endogenous miRNAs and delivers them to recipient cells with functional targeting capabilities. Cellular export of miRNAs to HDL was demonstrated to be regulated by neutral sphingomyelinase. Reconstituted HDL injected into mice retrieved distinct miRNA profiles from normal and atherogenic models. HDL delivery of both exogenous and endogenous miRNAs resulted in the direct targeting of messenger RNA reporters. Furthermore, HDL-mediated delivery of miRNAs to recipient cells was demonstrated to be dependent on scavenger receptor class B type I. The human HDL–miRNA profile of normal subjects is significantly different from that of familial hypercholesterolemia subjects. Notably, HDL–miRNA from atherosclerotic subjects induced differential gene expression, with significant loss of conserved mRNA targets in cultured hepatocytes. Collectively, these observations indicate that HDL participates in a mechanism of intercellular communication involving the transport and delivery of miRNAs. Human high-density lipoprotein (HDL) is found to transport endogenous miRNAs in plasma and to deliver them to recipient cells where they can silence mRNA reporter targets. HDL miRNAs isolated from atherogenic mice models or human atherosclerotic subjects induce changes in gene expression different from the ones seen with control HDL–miRNA populations.